THE HYPERREALITY AND SIMULACRA THEORY OF JEAN BAUDRILLARD: ON FASHION TRENDS IN TIKTOK - Teuku Ryan Firmansyah; Muttaqin, Khoirul; Layli Hidayah; Itznaniyah Umie Murniatie (ELite Journal : International Journal of Education, Language and Literature, 2024)
The rapid development of the times impacts the changing culture of society. The tendency towards technology and social media has become a common thing in the current postmodern era. In the modern era, humans tend to use technology and mass media as something they must do. This research aims to find facts from Jean Baudrillard’s theory regarding hyperreality and simulacra that are currently occurring in people’s lives. The author uses a qualitative approach with descriptive methods. Descriptive research aims to provide a comprehensive picture and clear exploration of a phenomenon or social reality that occurs. The results of the research are that people wear shimmery clothes because they want to achieve their existence as simulacra. People choose social media when wearing simulacra clothes on TikTok social media as hyperrality. This research concludes that simulacra and hyperreality occur in society which give rise to cultural shifts and have an impact on previous societal habits and tendencies towards technology and social media.